2017
DOI: 10.2106/jbjs.16.01395
|View full text |Cite
|
Sign up to set email alerts
|

Serum D-Dimer Test Is Promising for the Diagnosis of Periprosthetic Joint Infection and Timing of Reimplantation

Abstract: Diagnostic Level II. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
275
5
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 279 publications
(306 citation statements)
references
References 29 publications
10
275
5
9
Order By: Relevance
“…It has been reported that D-dimer sharply increases up to double levels and decrease to the baseline level within a short time during early postoperative period of TJA, and this dynamic change is more rapid than ESR and CRP [34,35]. Shahi et al [13] found that the sensitivity, specificity, and the cutoff value of plasma D-dimer were 89%, 93%, and 850 ng/mL, respectively, for detecting PJI. He considered plasma D-dimer is better than ESR and CRP in the diagnosis of PJI, and the D-dimer test has a great utility for determining the optimal timing of reimplantation [13].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been reported that D-dimer sharply increases up to double levels and decrease to the baseline level within a short time during early postoperative period of TJA, and this dynamic change is more rapid than ESR and CRP [34,35]. Shahi et al [13] found that the sensitivity, specificity, and the cutoff value of plasma D-dimer were 89%, 93%, and 850 ng/mL, respectively, for detecting PJI. He considered plasma D-dimer is better than ESR and CRP in the diagnosis of PJI, and the D-dimer test has a great utility for determining the optimal timing of reimplantation [13].…”
Section: Discussionmentioning
confidence: 99%
“…Shahi et al [13] found that the sensitivity, specificity, and the cutoff value of plasma D-dimer were 89%, 93%, and 850 ng/mL, respectively, for detecting PJI. He considered plasma D-dimer is better than ESR and CRP in the diagnosis of PJI, and the D-dimer test has a great utility for determining the optimal timing of reimplantation [13]. However, they focused more on the role of D-dimer in the diagnosis of PJI and did not differentiate the role of D-dimer in the type of PJI (acute or chronic) [13,34].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Serum D-dimer is another biomarker that has shown very promising results for diagnosing PJI. Shahi et al [30] in their prospective study showed that serum D-dimer outperforms both ESR and CRP for diagnosing PJI with a sensitivity of 89% and a specificity of 93%.…”
Section: Serum Biomarkersmentioning
confidence: 99%